REFA (REHABILITASI FRIEDREICHâS ATAXIA) SEBAGAI UPAYA PENINGKATAN KUALITAS HIDUP PENDERITA DI KECAMATAN AMPEL BOYOLALI - Zaenabu, Lina; Labetubun, Nia Sahra; Sitta, Alfi Nurmas; Dewanti, Ajeng Aprilia (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Genetic disorders are the most common coordination in the world is Fridreich s ataxia (FA). In Indonesia FA obtained Boyolali Ampel area. FA is progressive and has not found specific drugs for FA. Symptoms and accompanying complications can be treated with physical exercise. Physical exercise can reduce the progression of symptoms and helps maintain body functions as long as possible. The level of knowledge of patient and public awareness about the FA in Boyolali Ampel sub-district is still lacking. Improving the quality of life and slow the worsening condition of the patient FA. Divided into three phases, namely the preparation, implementation, and follow-up. In the implementation phase given counseling or education, provide motivation and physical exercise through video playback, provide physical exercise posters, and pocket books to be handgrip patients, provision of aids to patients, perform a physical examination, and renovate one of the stalls where people work. In the follow-up stage of the final observation assessment to measure the success of this program and reinforce the benefits of patients. Improved quality of life is evident from the scores of healthy physical (exercise 58.33% to 93.33%, the cleanliness of 66.7% to 85%, and the nutritional 71.67% to 78.33%), healthy social (65% to 75%), a healthy spiritual (85% to 91, 67%), support family members as the cadre (71.67% to 93.33%), the increase in scores independence and decrease depression scores. Worsening condition of the patient can be slowed as evidenced by an increase in the percentage of physical exercise. Physical exercise and family support is very influential in improving the quality of life of patients.